2014
DOI: 10.1103/physrevlett.113.267602
|View full text |Cite
|
Sign up to set email alerts
|

Duality of Topological Defects in Hexagonal Manganites

Abstract: We show that the spontaneous symmetry breaking in multiferroic hexagonal manganites can be chemically manipulated to yield two complementary ground states: the well-known ferroelectric P6(3)cm and an antipolar P3c phase. Both symmetry breakings yield topologically protected vortex defects, with the antipolar vortices dual to those of the ferroelectric. This duality stems from the existence of 12 possible angles of MnO5 tilting, and broad strain-free walls with low energy spontaneously emerge through an interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 34 publications
7
54
0
Order By: Relevance
“…Note that the P 3c1 structure has not been observed as a bulk phase in stoichiometric InMnO 3 , but was recently reported at the walls separating the partially undistorted antipolar domains in the Ga-doped material. 15 The presence of an oxygen vacancy causes significant changes in the density of states, particularly near the Fermi level, as shown in Fig. 3(c).…”
Section: Oxygen Defectsmentioning
confidence: 95%
See 4 more Smart Citations
“…Note that the P 3c1 structure has not been observed as a bulk phase in stoichiometric InMnO 3 , but was recently reported at the walls separating the partially undistorted antipolar domains in the Ga-doped material. 15 The presence of an oxygen vacancy causes significant changes in the density of states, particularly near the Fermi level, as shown in Fig. 3(c).…”
Section: Oxygen Defectsmentioning
confidence: 95%
“…Previous ab initio studies 14,15 found that the ground-state energetics are sensitive to the choice of exchange-correlation functional. For spin-polarized Perdew-Burke-Ernzerhof functionals (PBE), 36 for example, a non-polar ground state is slightly favored for stoichiometric InMnO 3 , whereas the spin-polarized PBE plus Hubbard U (GGA+U) method yields a ferroelectric ground state, in agreement with the likely experimental situation.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations